Does identity affect aspirations in rural areas? An examination from the lens of caste and gender - Alvi, Muzna (International Food Policy Research Institute, 2018)
Presented by Muzan Alvi (IFPRI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.